Quantitation and Identification of Therapeutic Anti-CD22 Monoclonal Antibodies in a Cell-Based ELISA Method - Shengyu Fu; Qi Zhao (Antibodies, 2022)
Since they lack native soluble membrane antigens, the analysis and selection of antigen-specific antibodies are commonly performed on whole live cells. Here, we have developed a simple and convenient enzyme-linked immunosorbent assay (ELISA) based on cell membrane antigens. Soluble cell membrane proteins isolated from Raji cells were immobilized on the polystyrene microplate, which permitted the assessment of a therapeutic anti-CD22 monoclonal antibody. The experiments showed less variability in the intra-assay. Compared to the living cell ELISAs, the advantage of the assay is avoiding cell losses and high variation of optical density (OD) readings. We provide a quantitative and reproducible ELISA that can be potentially applied to the development of specific antibodies against cell surface antigens.